Analisis Kerusakan Jalan Menggunakan Metode PCI Dan Metode Bina Marga (Studi Kasus Jalan Ahmad Yani Kecamatan Kapas Kabupaten Bojonegoro) - Santosa, Rudy; Sujatmiko, Bambang; Krisna, Fajar Aditya (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2021)
Roads are an important infrastructure in transportation that can affect the progress of the economic, social, cultural, and political fields in a region. However, the planned age of the road is not in accordance with what is happening in the field. The purpose of this study was to assess the pavement condition of Jalan Ahmad Yani, Kapas District, Bojonegoro Regency. The method used in this study is a qualitative and quantitative method which refers to the PCI (Pavement Condition Index) method and the Bina Marga method. Jalan Ahmad Yani, Bojonegoro Regency, with a length of 2.6 km is divided into several segments with a size of 200 x 7.5 m per segment. Each segment is evaluated by measuring the dimensions, identifying the type and level of damage to obtain the PCI value and the Bina Marga value. The results showed that there were 6 types of damage, including Patching and Utility cut Patch damage of 29.20%, Potholes of 17.88%, Weathering and Raveling of 6 .20%, Polished Aggregate 6.57%, Meandering Crack 25.91%, and Alligator Cracks 14.23%. For the assessment of the condition of Jalan Ahmad Yani, Kapas Subdistrict, Bojonegoro Regency using the Bina Marga method and the PCI method, it turned out that the results were relatively similar, the PCI method resulted in a more detailed assessment with "GOOD" results by means of periodic handling, while the Bina Marga method resulted in an assessment which is better with the results of "Priority 7" where the way of handling these priorities is by means of routine maintenance. Therefore, it can be concluded that the road damage assessment method is recommended using the PCI method. Meanwhile, the types of maintenance that can be carried out to improve the service level of the road include adding additional layers, repairing and adding drainage, filling cracks with hot mix asphalt, and patching any damage to prevent it from spreading.